Esperanza Rising - Ryan, Pam Munoz; Nang Chan Yeema (New York, USA Scholastic Inc., 2001)
Esperanza believed her life would be wonderful forever. She would always live on her family's ranch in Mexico. She would always have fancy dresses and a beautiful home filled with servants. Papa and Abuelita would always be with her.
Keywords: Adult Fiction